A new hybrid uncertain analysis method for structural-acoustic systems with random and interval parameters. (15th October 2016) - Wang, Mingjie; Huang, Qibai
Highlights: The response of the hybrid uncertain structural-acoustic system is investigated. PCRSM is proposed for the prediction of the system with the hybrid uncertainties. PCRSM has the ability to handle the pure random or interval uncertainty. PCRSM is capable of solving black-box type problems. Abstract: This paper proposes an uncertain analysis method named Polynomial Chaos Response Surface method (PCRSM) for uncertainty propagation in structural-acoustic system containing hybrid uncertainties. The polynomial chaos expansion method combined with the response surface methodology is employed to handle the random and interval uncertainty. The PCRSM does not require efforts to modify model equations due to its non-intrusive characteristic. The PCRSM is also able to predict the response of the system with only random or only interval uncertainty. The numerical results demonstrate that the PCRSM is effective and computationally efficient.